(untitled) (Medical Forum Monthly, 2023)
Objective: To review the presentation and evaluate the radiographic and functional outcome of developmental dysplasia of hip (DDH) in older children treated by triple procedure surgery, consisted of open reduction, Salter Innominate Osteotomy (SIO), femoral shortening and derotation Osteotomy. Study Design: Observational / descriptive study. Place and Duration of Study: This study was conducted at the BMC Hospital Quetta from January 2013 to December 2015. Materials and Methods: We assess the efficacy and safety of underwent triple procedure treatment of DDH in older children. The study series comprising 22 patients (25 hips).Patients were classified pre-operatively according to the Tonnis Classification, and post-operative functional evaluation was performed using modified Mackay’s scoring system, while radiographic assessment considered Severin scoring method. Results: The average age at presentation was 5.60 years and the male to female ratio was 2:46 months. While the average follow-up were 16.4 months. The final outcome was successful in 19 hips (76%) in 16 patients. Patients younger than 5-6 years of age had a better radiological and clinical outcome as compared to older children. Although in the outcome of clinical and radiological assessment there were no significant different between group-I and group-II. Conclusions: Late presentation of DDH is still common in Quetta, Balochistan, which necessitates Triple procedure operative management given frequent occurrences of best result in younger children. Early diagnosis and surgical interventions is therefore imperative in the successful treatment of patients suffering from DDH.